Clear cell sarcoma of kidney: an uncommon paediatric neoplasm-two case reports and review of literature - Gurusamy, Veeraraghavan; Karnan, Indumathi; Sadagopan, Pappathi (International Journal of Contemporary Pediatrics, 2016)
Clear cell sarcoma of kidney is an uncommon neoplasm accounting for approximately 5% of all pediatric renal neoplasms, with a peak incidence between 1-3 years of age. Males are most commonly affected (M:F ratio – 2:1). It is a highly malignant neoplasm with a high propensity than other renal neoplasms to metastasize to bones, hence originally called as bone-metastasizing renal tumour of childhood by Marsden and Lawler. We describe here 2 case reports of clear cell sarcoma of kidney.